2016
DOI: 10.1037/apl0000043
|View full text |Cite
|
Sign up to set email alerts
|

Out of control: A self-control perspective on the link between surface acting and abusive supervision.

Abstract: In this study, we examined how leaders' customer interactions influence their tendency to abuse their followers. Specifically, we drew from ego-depletion theory to suggest that surface acting during customer interactions depletes leaders of their self-control resources, resulting in elevated levels of abusive supervision. Furthermore, we hypothesized that the effect of surface acting on abusive supervision is moderated by leaders' trait self-control, such that leaders with high trait self-control will be less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
152
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(170 citation statements)
references
References 73 publications
5
152
1
1
Order By: Relevance
“…First, although research has found that abusive supervision is more likely to happen when supervisors are depleted and unable to control their impulses (Barnes et al 2015;Yam et al 2015), some instances of abusive supervision might be driven by ''rational weighting of the costs and benefits associated with abuse'' (Tepper et al 2012, p. 196). Research has shown that subordinates' attributes (e.g., negative affectivity and performance, Tepper et al 2006Tepper et al , 2011 are important factors determining supervisors' decisions of whom to abuse when they encounter negative experiences, we contribute to this line of research by drawing on the cognitive-neoassociationistic model of aggression and examining it as the product of negative affect and supervisor-subordinate relationship quality.…”
Section: Discussion General Discussion and Theoretical Implicationsmentioning
confidence: 98%
“…First, although research has found that abusive supervision is more likely to happen when supervisors are depleted and unable to control their impulses (Barnes et al 2015;Yam et al 2015), some instances of abusive supervision might be driven by ''rational weighting of the costs and benefits associated with abuse'' (Tepper et al 2012, p. 196). Research has shown that subordinates' attributes (e.g., negative affectivity and performance, Tepper et al 2006Tepper et al , 2011 are important factors determining supervisors' decisions of whom to abuse when they encounter negative experiences, we contribute to this line of research by drawing on the cognitive-neoassociationistic model of aggression and examining it as the product of negative affect and supervisor-subordinate relationship quality.…”
Section: Discussion General Discussion and Theoretical Implicationsmentioning
confidence: 98%
“…For example, researchers find that managers tend to experience ego depletion after dealing with customer complaints (Yam, Fehr, Keng-Highberger, Klotz, & Reynolds, 2016) and from serving as an ethical role model for their subordinates (Lin, Ma, & Johnson, 2016). Likewise, excessive workloads and pressure are likely to leave managers more depleted at work (Barnes, 2011;Barnes, Lucianetti, Bhave, & Christian, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Such typical managerial behaviors can consume managers' energy resources and result in ego depletion, “a state in which the self does not have all the [self‐control] resources it has normally” (Baumeister & Vohs, , p.2). For example, researchers find that managers tend to experience ego depletion after dealing with customer complaints (Yam, Fehr, Keng‐Highberger, Klotz, & Reynolds, ) and from serving as an ethical role model for their subordinates (Lin, Ma, & Johnson, ). Likewise, excessive workloads and pressure are likely to leave managers more depleted at work (Barnes, ; Barnes, Lucianetti, Bhave, & Christian, ).…”
mentioning
confidence: 99%
“…We use integrative self‐control theory (SCT) as an overarching theoretical framework for the current investigation (Kotabe & Hofmann, ; Lian, Yam, Ferris, & Brown, ). According to SCT, self‐control resolves conflicts between an impulsive desire (e.g., venting anger or frustrations) and adherence to a higher order goal, and enables one to refrain from acting upon the desire in favor of the higher goal (Yam, Fehr, Keng‐Highberger, Klotz, & Reynolds, ). It specifically entails “the overriding or inhibiting of automatic, habitual, or innate behaviors, urges, emotions, or desires that would otherwise interfere with goal‐directed behavior” (Muraven, Shmueli, & Burkley, , p. 524).…”
mentioning
confidence: 99%